Fibrinogen reflects severity and predicts outcomes in patients with sepsis and septic shock - Schupp, Tobias; Weidner, Kathrin; Rusnak, Jonas; Jawhar, Schanas; Forner, Jan; Dulatahu, Floriana; Brück, Lea Marie; Lübke, Johannes; Hoffmann, Ursula; Bertsch, Thomas; Behnes, Michael; Akın, Ibrahim (Blood coagulation & fibrinolysis, 2023)
The study investigates the diagnostic and prognostic value of fibrinogen and the albumin-to-fibrinogen-ratio (AFR) in patients with sepsis and septic shock. Limited data regarding the prognostic value of fibrinogen and AFR during the course of sepsis or septic shock are available. Consecutive patients with sepsis and septic shock from 2019 to 2021 were included monocentrically. Blood samples were retrieved from the day of disease onset (day 1), as well as on day 2 and 3. Firstly, the diagnostic value of fibrinogen and the AFR for the diagnosis of a septic shock was tested. Secondly, the prognostic value of fibrinogen and AFR was tested with regard to the 30-day all-cause mortality. Statistical analyses included univariable t-tests, Spearman's correlations, C-statistics, Kaplan-Meier and multivariable Cox regression analyses. Ninety-one patients with sepsis and septic shock were included. With an area under the curve (AUC) of 0.653-0.801, fibrinogen discriminated patients with septic shock from those with sepsis. In the septic shock group, fibrinogen levels were shown to decrease from day 1 to 3 (median decrease 41%). In line, fibrinogen was a reliable predictor for 30-day all-cause mortality (AUC 0.661-0.744), whereas fibrinogen levels less than 3.6 g/l were associated with an increased risk of 30-day all-cause mortality (78 vs. 53%; log rank P = 0.004; hazard ratio = 2.073; 95% confidence interval 1.233-3.486; P = 0.006), which was still observed after multivariable adjustment. In contrast, the AFR was no longer associated with the risk of mortality after multivariable adjustment. Fibrinogen was a reliable diagnostic and prognostic tool for the diagnosis of septic shock as well as for 30-day all-cause mortality and superior compared with the AFR in patients admitted with sepsis or septic shock.